GP223 Creatine deficiency disorders the all-ireland experience. (June 2019) - Howard, Caoimhe; Monavari, AA; Knerr, Ina; Pastores, Gregory; O'Sullivan, Siobhan; Crushell, Ellen
Abstract : Background: Cerebral creatine deficiency is caused by rare inherited disorders of either creatine biosynthesis (i.e. guanidinoacetate methyltransferase (GAMT) and arginine:glycine amidinotransferase (AGAT) deficiency), or creatine transport (i.e. creatine transporter deficiency, CRTR). Clinical features include variable hypotonia, speech delay (often the dominant feature), seizures, extrapyramidal signs and behavioural issues. Patients may have feeding issues and low weight. There is some evidence that early treatment of these disorders is successful, particularly in GAMT and AGAT deficiency. Method: A retrospective chart review was undertaken of all patients who have attended the national metabolic referral centres at Dublin and Belfast with creatine deficiency. Details recorded included history, clinical findings, treatments and results of laboratory, genetic and radiological investigations. Results: Six patients with current ages between 5 and 29 years were identified with a confirmed disorder of creatine metabolism – four male patients with X-linked CRTR and two female siblings with autosomal recessive GAMT deficiency. Initial diagnosis was made on urine biochemistry (analysis of creatine/creatinine and guanidinoacetate) in two patients, on MR spectroscopy in three patients (creatine peak significantly reduced) and via exome sequencing in one patient. All cases were confirmed biochemically and genetically. Despite onset of symptoms before the age of 2 years, mean age at diagnosis was 7.5 years, with range from 20 months to 17 years. Six patients had significant developmental delay, particularly in the domains of speech and behaviour. Three of the patients have weights <9th centile. Five of the patients had documented head circumferences, and all were normocephalic proportional to height and weight. Both patients with GAMT deficiency had epilepsy which responded to treatment with creatine and ornithine. Three patients with CRTR also had epilepsy. Two patients with CRTR have been treated with creatine and creatine/arginine/glycine/S-adenosylmethionine in combination, without notable effect on clinical symptoms or MR spectroscopy findings, which is in keeping with expectations for this condition. The four patients with CRTR are hemizygous for pathogenic mutations in the SLC6A8 gene, de novo in two patients and maternally inherited in another, one has not had parental testing. The siblings with GAMT deficiency are compound heterozygous for mutations in the GAMT gene. Conclusion: Although rare in Ireland, these treatable disorders are likely under-diagnosed. In a patient with developmental delay (particularly speech impairment) and behavioural difficulties, consideration should be given to sending a urine sample for analysis of creatine/creatinine ratio and guanidinoacetate, particularly if there is comorbid epilepsy.